ON DISCRETE STRUCTURE OF GEOLOGIC MEDIUM AND CONTINUAL APPROACH TO MODELING ITS MOVEMENTS - Sh. A. Mukhamediev (Геодинамика и тектонофизика, 2016)
This paper discusses the structure of a geologic medium represented by accessible lithified rocks and provides an overview of methods used to describe its movements. Two basic opinions are considered in the framework of the discussion: (1) an initially homogeneous and continuous geologic medium acquires the structure composed of blocks in the process of the geologic medium’s deformation/destruction/degradation, and (2) a geologic medium is composed of blocks (and often has hierarchic, active, energy-saturated features), and the continuity model is thus not valid for describing the geologic medium’s deformation. Proponents of the first point of view actively apply the standard or modified continuum model of a solid deformed body (SDB) in estimations of the stress-strain state, but the input parameters of this model do not contain any information on discreteness in principle. Authors who support the second opinion, either explicitly or implicitly assume that the block structure of the geologic medium, which is detectable by geological methods, makes a direct and unambiguous impact on all other mechanical properties of the geologic medium and, above all, on the nature of its movements.Based on results obtained by interpreting the data collected in our long-term field studies of rock fracturing, mathematical processing of GPS-measurements, and theoretical models, we agree with the concept of the geologic medium’s block structure, but argue that the geologic block-structure property is not acquired but congenital. Regarding sedimentary rocks, it means that the discrete structure has been already embodied in the rock before sediment lithification, regardless of the intensity of macroscopic deformations. A discrete structure is the form of the geologic medium existence and a cause of the congenital anisotropy of the geologic medium’s strength characteristics. Due to subsequent deformation of the geologic medium, some elements of the structure can be manifested more clearly, and the structure itself can become more complex due to secondary effects. At the same time, the structure of geologic blocks is not directly manifested in the spatial and temporal features of the recent movements in the geologic medium. However, it is not an obstacle to developing continuum models of such movements in the same way as, for instance, the adequacy of the continuum general theory of relativity is not denied in view of the discrete-hierarchical structure of the Universe.The key requirements to a model include its applicability, testability, confirmability/deniability of its predictions in the investigated space-time scale, and compliance with conservation laws. This paper briefly discusses the most important aspects of the continuum approach based on the concept of an effective continuous medium and, above all, the Cauchy continuum model, envisaging that the dynamic response of the medium in spatial descriptions is given only by the Cauchy symmetric stress tensor (T). In more general continuum models of the medium (such as moment, micropolar, micromorphic and other models), the dynamics of the medium may be characterized by asymmetric tensors of force and couple stresses.This paper refutes the unjustified criticism of the continuum model as such criticism is rooted in the mistaken identification of quite special assumptions or ways of setting the problems with the general principles of the continuity model. Special attention is given to critical comments received from supporters of the active geologic medium concept. The paper considers actual difficulties encountered in studies using the continuity model, specifically in coordinated descriptions of the medium containing mobile defects, as well as the medium that is subject to deformation due to movements on its structure, while this structure is hierarchical at any scale level, down to the zero level (which, in particular, concerns the fractal structure). Discussed are causes of some widespread misunderstandings and mistakes in the geoscience literature, as well as the occurrence of conditions facilitating the revival of Aristotle ideas and preNewton concepts in geology, which repeatedly gain the upper hand over the modern ideas of classical physics. The paper considers the problem of reconstruction of stresses in the geologic medium from in-situ kinematic indicators, specifically from irreversible slips. Attention is drawn to the fact that the currently dominating approach ‘imposes’ a priori speculative rules on the geologic medium, such as a relationship between stresses (to be estimated) and the slip directions. Under this approach, the conservation laws are inevitably ignored, which makes it impossible to interpret the obtained results in terms of stress. Under the alternative approach proposed earlier by the author of this paper, the conservation laws being taken into account allows not only to reconstruct the stress tensor field, but also to judge on the geologic medium rheology. It is concluded that rejecting the continuum approach a priori, with a reference to the geologic medium discreteness, is at least unconstructive.